Knowledge and Adoption of Complex Agricultural Technologies : Evidence from an Extension Experiment - Hörner, Denise (World Bank, Washington, DC, 2021)
In most of Sub-Saharan Africa, agricultural extension models have become more decentralized and participatory and thus, rely on effective farmer-to-farmer learning, while increasingly including non-traditional forms of education. At the same time, agricultural technologies become more complex and are now often promoted as integrated packages, likely to increase the complexity of the diffusion process. Based on a randomized controlled trial, this study assesses the effects of ‘farmer-to-farmer’ extension and a video intervention on adoption of a complex technology package among 2,382 smallholders in Ethiopia. Both extension-only and extension combined with video increase adoption and knowledge of the package, especially of its more complex components; although on average, there is no additional effect of the video intervention on adoption. Knowledge and the number of adopted practices also increase among farmers not actively participating in extension activities, suggesting information diffusion. For this group, the additional video intervention has a reinforcing effect, and particularly fosters adoption of the integrated package.